Strengthening music provision in early childhood education: a collaborative self-development approach to music mentoring for generalist teachers. (20th October 2019) - Barrett, Margaret S.; Zhukov, Katie; Welch, Graham F.
ABSTRACT: This paper reports an evaluation of a pilot programme of workplace music mentoring for generalist classroom teachers in eleven early childhood education settings in Australia. Mentoring in the arts in general and in music specifically is still under-researched despite a body of literature on approaches to mentoring, and descriptions of mentoring practices and outcomes. The pilot programme was created to increase access to music education for Australian children through establishing mentoring relationships between experienced specialist music teachers and generalist classroom teachers. The programme aimed to address a lack of music training during undergraduate teacher preparation and a perceived lack of confidence in music teaching and singing amongst generalist classroom teachers. The evaluation included semi-structured interviews with ten principals, seven mentors and nineteen mentees regarding their experiences. Three researchers conducted the thematic analysis of transcripts independently and refined the emerging themes through iterative discussions. Findings demonstrate that the workplace music mentoring delivered positive outcomes, enriching schools' music curricula, structuring locally relevant programmes, building resources, teacher music skills and confidence, and impacting positively on student learning and behaviour. This in-situ longitudinal mentoring model expands on traditional approaches to professional development for in-service teachers of music through a collaborative self-development approach.